Rates and outcomes of testing for lynch syndrome in a national colorectal cancer screening programme. (February 2023) - Cudmore, Jane; Kumar, Lakshman; O'Moráin, Neil; Cullen, Garrett; Horgan, Gareth; Aird, John; Sheahan, Kieran; Winter, Desmond C.; Kennelly, Rory; Leyden, Jan
Abstract: Background: Lynch Syndrome (LS), the most common cause of hereditary colorectal cancer (CRC), is characterised by pathogenic variants in mismatch repair (MMR) genes. Universal testing of all CRCs for LS can increase detection. Rates and outcomes of testing in Ireland's national CRC screening programme have not been examined previously. Methods: CRCs diagnosed at two screening sites between 2015 and 2020 were identified. Patient records were used to determine if CRCs had been tested for MMR deficiency and if detected, what downstream testing to rule out LS or genetic testing to confirm LS was undertaken. Results: Over five years, 206 CRCs were diagnosed. Testing for LS was carried out for 100% of CRCs at site A and 69% of CRCs at site B. Of CRCs tested for LS, 14 (8%) were MMR deficient. After downstream testing for BRAF mutation or hypermethylation of MLH1, three CRCs were identified as potentially LS-related. Of these two individuals declined genetic testing and one was lost to follow-up. Conclusions: By 2020 both sites had implemented universal testing of all CRCs for LS. A small number of individuals were identified as being eligible for genetic testing for LS, however those offered declined testing and one individual was lost to follow up. This highlights the importance of universal testing and the need for referral pathways to ensure all appropriate individuals are referred onwards to genetic services. Highlights: Universal testing of all colorectal cancers for Lynch Syndrome can increase detection From 2020 nearly all colorectal cancers at two Irish colorectal cancer screening sites were tested The rate of mismatch deficiency was 7% in our screening population 1.5% of those with colorectal cancer had an indication for genetic testing, however no individual proceeded to testing Our study would support the development of clear national diagnostic guidelines for LS and referral pathways to genetic services.